2010
DOI: 10.2989/16085906.2010.517478
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting first-month adherence to antiretroviral therapy amongHIV-positive adults in South Africa

Abstract: This study explores the influence of baseline factors on first-month adherence to highly active antiretroviral therapy (HAART) among adults. The study design involved a review of routinely collected patient information in the CAPRISA AIDS Treatment (CAT) programme, at a rural and an urban clinic in KwaZulu-Natal Province, South Africa. The records of 688 patients enrolled in the CAT programme between June 2004 and September 2006 were analysed. Adherence was calculated from pharmacy records (pill counts) and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…Our cohort comprised individuals with a higher median CD4 count at ART initiation than in those studies and findings corroborate that seen in high income countries reported in the systematic review by Bock et al [17]. WHO recommends universal test and treat for HIV [1]; South Africa has already adopted this recommendation Using either adherence measure, men had more than double the odds of sub-optimal adherence compared with women, similar to findings reported in two studies in Tanzania [19] and South Africa [20]. We observed a high out-migration rate which was cyclical in nature within the TasP trial.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our cohort comprised individuals with a higher median CD4 count at ART initiation than in those studies and findings corroborate that seen in high income countries reported in the systematic review by Bock et al [17]. WHO recommends universal test and treat for HIV [1]; South Africa has already adopted this recommendation Using either adherence measure, men had more than double the odds of sub-optimal adherence compared with women, similar to findings reported in two studies in Tanzania [19] and South Africa [20]. We observed a high out-migration rate which was cyclical in nature within the TasP trial.…”
Section: Discussionsupporting
confidence: 80%
“…Adherence at each visit was plotted over the first 12 months after ART initiation; during this period, adherence was expected to be documented at 13 visits (2,4,8,12,16,20,24,28,32,36,40,44, 48 weeks post ART initiation). Random effects logistic regression was used to examine the association between CD4 count at initiation and sub-optimal adherence at each visit.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study demonstrated that age, the level of education achieved, employment or nonemployment, HIV disclosure to family, and comfortability in taking ART in the presence of others are the conditions that will effect ART adherence. This is contradictory to the finding of Maqutu et al33 However, demographic factors are closely linked to socioeconomic status, which encompasses access to resources such as educational opportunities, living conditions, social support, and health facilities, which are similarly observed in the literature of Rachlis et al’s review on livelihood and ART adherence at its early stage 34…”
Section: Discussionmentioning
confidence: 67%
“…Younger age, lower education, and lower income were all shown to be associated with worse therapeutic and immune responses due to the low frequency of adherence and poor access to healthcare services [20][21][22]. However, previous studies have also demonstrated that decreased adherence was associated with higher baseline CD4 counts [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%